A prospective cohort study of physical activity in relation to lung cancer incidence among Black women. (June 2022) - Bethea, Traci N.; Dash, Chiranjeev; Adams-Campbell, Lucile L.
Abstract: Background: Black women have higher lung cancer incidence and mortality rates despite a lower smoking prevalence than White women. Physical activity may reduce lung cancer risk through several pathways, including the immune and inflammatory systems, as well as those with effects on sex hormones and metabolism. Methods: We examined vigorous physical activity, walking for exercise, sitting watching television, and metabolic equivalents (METs) in relation to lung cancer risk among 38, 432 participants in a prospective cohort of Black women. We used Cox proportional hazards models adjusted for covariates to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: In 1995–2017, 475 incident lung cancer cases accrued. Participants who engaged in ≥ 1 h/week of vigorous physical activity or expended the highest tertile of METs experienced a decreased risk of lung cancer (HR: 0.85, 95% CI: 0.65–1.10; 0.89, 0.68–1.18; respectively). An increased risk was observed for sitting watching television (≥1 h/week: 1.27, 0.72–2.21). In stratified models, an inverse association between walking for exercise and lung cancer risk was only present among former smokers (≥1 h/week: 0.71, 0.52–0.98), while inverse associations between vigorous physical activity (≥1 h/week: 0.45, 0.28–0.73) and METs (tertile 3: 0.54, 0.34–0.85) and lung cancer risk were present among smokers with ≥ 20 pack-years. Conclusion: Physical activity may play a role in reducing lung cancer risk among Black women, particularly among smokers. Future studies should explore biologic mechanisms whereby physical activity may influence carcinogenesis and investigate the role of exercise interventions in reducing lung cancer risk among smokers. Highlights: Racial differences in lung cancer are not explained by smoking prevalence. We found that walking for exercise reduced lung cancer risk among former smokers. Vigorous exercise was inversely associated with cancer risk in a subset of smokers. Physical activity may reduce lung cancer risk among smokers.